Congress Memorys of the "I International Congress in Neurology, Neurosurgery, Neuropsychiatry and Clinical, Functional and Advanced Neuropsychology" - Carlos Alberto Hurtado González (Interdisciplinary Journal of Epidemiology and Public Health, 2023)
Congress Memorys of the "I International Congress in Neurology, Neurosurgery, Neuropsychiatry and Clinical, Functional and Advanced Neuropsychology"